2016
DOI: 10.1371/journal.pone.0151652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Exercise Programme on Functional Capacity, Body Composition and Risk of Falls in Patients with Cirrhosis: A Randomized Clinical Trial

Abstract: Patients with cirrhosis often have functional limitations, decreased muscle mass, and a high risk of falls. These variables could improve with exercise. The aim was to study the effects of moderate exercise on functional capacity, body composition and risk of falls in patients with cirrhosis. Twenty-three cirrhotic patients were randomized to an exercise programme (n = 14) or to a relaxation programme (n = 9). Both programmes consisted of a one-hour session 3 days a week for 12 weeks. At the beginning and end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
147
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(155 citation statements)
references
References 35 publications
5
147
0
3
Order By: Relevance
“…Prior studies, consisting of 6‐60 participants, have mainly focused on face‐to‐face, supervised exercise interventions in the hospital setting and in patients without significant liver failure warranting LT . In agreement with our findings, the safety, acceptability, and adherence of variable exercise programs in patients with MELD scores of 9‐13 was considered satisfactory . Similar to our patient demographic, a recent French study of 13 patients on the LT waiting list (average age, 51 years; MELD, 13) reported that 12 weeks of exercise intervention increased aerobic capacity, as assessed by cardiopulmonary exercise testing (oxygen consumption [VO 2 ] peak) and the 6‐minute walk test .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Prior studies, consisting of 6‐60 participants, have mainly focused on face‐to‐face, supervised exercise interventions in the hospital setting and in patients without significant liver failure warranting LT . In agreement with our findings, the safety, acceptability, and adherence of variable exercise programs in patients with MELD scores of 9‐13 was considered satisfactory . Similar to our patient demographic, a recent French study of 13 patients on the LT waiting list (average age, 51 years; MELD, 13) reported that 12 weeks of exercise intervention increased aerobic capacity, as assessed by cardiopulmonary exercise testing (oxygen consumption [VO 2 ] peak) and the 6‐minute walk test .…”
Section: Discussionsupporting
confidence: 88%
“…Prior studies, consisting of 6‐60 participants, have mainly focused on face‐to‐face, supervised exercise interventions in the hospital setting and in patients without significant liver failure warranting LT . In agreement with our findings, the safety, acceptability, and adherence of variable exercise programs in patients with MELD scores of 9‐13 was considered satisfactory .…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the broader chronic disease literature, the experimental and clinical evidence for a benefit of exercise in cirrhosis is promising. Several small clinical trials have demonstrated significant improvements in muscle health (mass, strength, functional capacity), quality of life, fatigue, cardiopulmonary fitness and reductions in the hepatic venous pressure gradient, without adverse events . Unfortunately, most patients (63%‐92%) included in these trials were cirrhosis CP‐A, while patients at the lower end of physical deconditioning (CP‐B/C) have not been evaluated systematically so far .…”
Section: Management Of Malnutrition and Sarcopenia In Cirrhosismentioning
confidence: 99%
“…In this study, patients performed aerobic exercise for 12 weeks at moderate intensity (heart rate, 60%‐70% of maximum) and received leucine supplementation . In a recent study, aerobic exercise performed for 12 weeks, without any nutritional supplementation, led to a significant decrease in body fat ( P = 0.003), an increase in lean mass ( P = 0.01), and an increase in functional capacity . Furthermore, aerobic exercise combined with caloric restriction attenuated loss of FFM from 25% to 11% .…”
Section: Management Issues In Sarcopeniamentioning
confidence: 99%